2006
DOI: 10.1097/01.yic.0000188216.92408.69
|View full text |Cite
|
Sign up to set email alerts
|

Amisulpride treatment of clozapine-induced hypersalivation in schizophrenia patients: a randomized, double-blind, placebo-controlled cross-over study

Abstract: The beneficial effect of sulpiride augmentation of clozapine therapy for treatment-resistant schizophrenia patients is enhanced by its antisalivatory effect on clozapine-induced hypersalivation (CIH). Amisulpride, similar to sulpiride, is a substitute benzamide derivative with higher selective binding to the D2/D3 dopamine receptor. We hypothesized that add-on amisulpride would also be beneficial in controlling CIH. In a randomized, double-blind, placebo-controlled cross-over study, 20 clozapine-treated schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…Our study and some other publications have demonstrated that substitute benzamide derivatives both with higher selective binding to the D 2 /D 3 dopamine receptors (such as sulpiride or amisulpride) and a reversible selective monoamine oxidase inhibitor-A (moclobemide) may be effective as treatment of CIS (Croissant et al 2005;Kreinin et al 2005Kreinin et al , 2006Kreinin et al , 2009Praharaj et al 2009). …”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…Our study and some other publications have demonstrated that substitute benzamide derivatives both with higher selective binding to the D 2 /D 3 dopamine receptors (such as sulpiride or amisulpride) and a reversible selective monoamine oxidase inhibitor-A (moclobemide) may be effective as treatment of CIS (Croissant et al 2005;Kreinin et al 2005Kreinin et al , 2006Kreinin et al , 2009Praharaj et al 2009). …”
Section: Methodsmentioning
confidence: 72%
“…Previous studies (Kreinin et al 2005(Kreinin et al , 2006(Kreinin et al , 2009) demonstrated effi cacy of three medications from group of substitute benzamide derivatives in treatment of CIS. We suggest that the antisalivation activity of this group of medications is most likely related to its peripheral activity for reducing gastric acid secretion.…”
Section: Discussionmentioning
confidence: 98%
“…10 The effective dose ranged from as low as amisulpride 50 mg/d 9 to 400 mg/d used in Kreinin et al 10 study. In our case, response was noted after 150 mg/d which resulted in significant reduction in daytime sialorrhea and improvement in speech.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, amisulpride, a potent D 2 and D 3 antagonist, reduces clozapine-induced hypersalivation, but the mechanism remains unknown. 51 The mechanism of clozapine-induced hypersalivation needs to be clarified further to find effective treatment for this adverse effect.…”
Section: Discussionmentioning
confidence: 99%